Change of Leadership in AACINI: Challenges and Perspectives for Argentine Industrial Engineering (AACINI - International Journal of Industrial Engineering, 2023)
As the new president of AACINI, I address the readers of RIII to greet them and express my gratitude to Mr. Miguel Rissetto, for his tireless work and for setting the bar very high.Industrial engineering in Argentina faces challenges such as accreditation according to new standards and competency-based education. AACINI collaborates with experts in university assessment and deans of engineering in this process. At this juncture, we are confronted with the need to prepare students to work in both large corporations and SMEs, fostering an entrepreneurial spirit.In this new role, I commit to tackling the challenges in industrial engineering education, promoting comprehensive student development, and strengthening the association's position in the legal arena.
Keywords: AACINI; Industrial Engineering; Challenges; XVI COINI 2023